Prediction of the allergic mechanism of haptens via a reaction-substructure-compound-target-pathway network system. (15th December 2019) - Di, Peiwen; Wu, Zengrui; Yang, Hongbin; Li, Weihua; Tang, Yun; Liu, Guixia
Highlights: A network system was developed to predict reactions, targets and pathways of haptens. It is the first time to explore the relationships between reactions and skin targets. 12 key substructures were identified to determine the protein binding reactions. 33 skin targets and 12 pathways were acquired to understand the allergic mechanism. Abstract: Skin sensitization, frequently leading to allergic contact dermatitis (ACD), is authenticated to be a significant endpoint in the field of drug discovery and cosmetics. The initiation of ACD, also known as the skin sensitization mechanism, has been documented as an adverse outcome pathway (AOP), which can be studied experimentally and computationally. In this study, we collected 154 haptens and applied systems toxicology methods to develop a reaction-substructure-compound- target-pathway network system. For the collected haptens, their key substructures were identified and associated with their protein binding reactions. The targets of haptens, including the known targets collected from four databases and the potential targets predicted via our balanced substructure-drug-target network-based inference (bSDTNBI) method, were matched to skin proteins to obtain skin targets. The dermatitis-related pathways were enriched and were subject to literature verification. The network system we developed can be applied to predict the reactions, targets and pathways of new haptens, which contributed to evaluating chemical safety and optimizing chemical structures. The study of skin sensitization mechanism is helpful for understanding the skin immunity and resisting ACD.